Kebijakan Formulasi Pertanggungjawaban Pidana Terhadap Penanganan Malpraktek Yang Dilakukan Oleh Dokter - Ida Ayu Dwi Wirautami; I Ketut Rai Setiabudhi (Fakultas Hukum, Universitas Warmadewa, 2022)
The rise of malpractice cases in Indonesia occurs due to the fault or negligence of a doctor in an effort to take medical action against patients. The purpose of this paper is to find out related to criminal liability for the handling of malpractice carried out by doctors based on law no. 29 of 2004 concerning the practice of medicine and the Criminal Code as well as criminal law arrangements for doctors who commit malpractice acts in the future. Normative legal research in this study departs from vague norms that do not explain specifically the policy of formulating criminal liability for the handling of malpractice carried out by doctors. As a result of this writing, there is no criminal liability policy for the handling of malpractice carried out by doctors clearly written in the Criminal Code and the Medical Practice Law, so it is felt that it is difficult to solve problems related to malpractice. The regulation of malpratics in the future is to make or update formulations and orientations related to laws and regulations regarding criminal acts or acts of medical malpractice and reformulate subsequent regulations through penal mediation as an ius constituendum policy in the context of updating criminal law in Indonesia.